Energy and Development Report 2001 - Energy and the Environment - World Bank (Washington, DC, 2014)
This 2001 Energy and Development Report reflects on the progress made since July 1999, when the need to include environmental concerns in energy sector development was acknowledged. The review looks at the context in which the energy, and environment debate is now set, and examines the primary outcomes of the strategy in relative depth. The second part reviews ways to create the framework for energy and environment, by enhancing capacity building, the knowledge base, and dissemination practices, through case studies and perspectives on sustainable energy systems. Reducing air pollution is further explored in the context of facilitating the transition from traditional, to modern fuels, by improving access to modern energy, while protecting the health of - mainly - urban residents from air pollution. In addition, through case studies on district heating, power distribution, and, initiatives regarding gas flaring reduction, the report focuses on the promotion of environmentally, sustainable development of energy resources, and on mitigating the potential - adverse - impact of energy uses on climate change. Future issues of concern include the trade-offs between the poverty, and environmental agendas in the energy sector, environmental regulation, climate change, and building partnerships.